Direct Measurement of ATP-Dependent Proton Concentration Changes and Characterization of a K+-Stimulated ATPase in Pea Chloroplast Inner Envelope Vesicles. - Shingles, R. (1994)
Inner envelope membrane vesicles prepared from pea (Pisum sativum L. var Laxton's Progress No. 9) chloroplasts have K+-stimulated ATPase activity with a pH optimum of 8.4. ATP addition to inner envelope vesicles loaded with pyranine caused a decrease in pyranine fluorescence that was consistent with internal acidification. The transmembrane pH change induced by the addition of 5 mM ATP was about 0.4 unit. Measurement of phosphate released by ATP hydrolysis paralleled the pH change, indicating that intravesicular acidification was linked to ATPase activity. Vanadate, molybdate, N-ethylmaleimide, and dithiothreitol inhibited ATP-dependent vesicle acidification completely, whereas ATPase activity was only partially inhibited. These data indicate that pea chloroplast inner envelope vesicles contain a proton translocating ATPase and that the pyranine-loading method can be utilized to study directly ATP-dependent H+ transport across these membranes.